Investigating a Substance Abuse Screening in a Trauma Setting. Issue 10 (October 2021) - Tuli, Rahul; Romero, Stephanie Anne; Figueroa, Cesar; Tay, Erika; Saadat, Soheil; Barrios, Cristobal
Introduction: Drug and alcohol consumption are often associated with trauma-related injuries. Various studies have been conducted which have shown the benefits of screening and brief intervention (SBI) tools for alcohol consumption. Despite their success, there are few SBI tools utilized for substance use and minimal reports of computerized versions. We hypothesized that a computerized SBI tool for drug use would be effective at identifying patients at risk of substance abuse in a trauma setting. Methods: This was a prospective evaluation of a computerized alcohol and drug screening and brief intervention survey derived from the National Institute on Drug Abuse. The survey was given to all eligible trauma patients at UCI's Level 1 trauma facility between February 2019 and March 2020. Based on self-reported answers, a substance involvement (SI) score was generated which classified a patient's drug abuse risk as none (0), low (1-3), moderate (4-26), or high (27+). Statistical tests were then used to examine associations between demographic variables and risk categorization. Results: A total of 1801 patients completed the entire survey. Of those, 346 (19.3%) patients reported use of illicit drugs: 10 for non-medical prescription use (.6%), 308 (17.1%) for non-prescription drug use, and 28 (1.6%) for both. Secondary analysis revealed a greater number of males were eligible for further SI assessment (25.1% vs 11.0%, P < .001). Of those, a greater proportion of men were classified as moderate/high risk (81.6% vs 61.5%, P < .001). Further breakdown revealed a greater proportion of patients ≤25 years old reported use of drugs compared to >85 years old (37.0% vs .5%, P < .001). In contrast to the self-reported data, there was an overall positive rate of toxicology of 48.51%. Conclusion: The analysis shows that the electronic survey identifies patients at risk of drug abuse, allowing for real-time intervention. Furthermore, it is granular enough to specify at-risk groups. However, a lower self-reported rate, as expected, was elucidated. Further studies to evaluate for improved screening and targeted intervention are warranted.